RESOURCES AND COMMUNICATIONS OPTIMALIZATION IN EDUCATIONAL MARKETING STRATEGY - Zuhaeda, Noor Fuadiyah (EARR (Educational Administration Research and Review), 2019)
In the era of globalization, adopting the concept of business marketing to face competition among educational institutions is something that cannot be avoided. The public demand for high-quality education, satisfactory customer service, and school’s resources become the basis of consideration for the educational institution in determining its marketing strategy. Optimal educational resources management and institution’s ability to communicate with customers and communities are the keys to effectively implement educational marketing strategies. The purpose of this literature review is to obtain a thorough understanding of resource optimization in education marketing strategies as an effort to increase customer and maintain customer loyalty.